Breast cancer screening in the Czech Republic: time trends in performance indicators during the first seven years of the organised programme - Brabec Petr; Klimes Daniel; Buresova Lucie; Bartonkova Helena; Skovajsova Miroslava; Danes Jan; Majek Ondrej; Kozeny Pavel; Dusek Ladislav (BMC, 2011)
Abstract Background The Czech Breast Cancer Screening Programme (CBCSP) was initiated in September 2002 by establishing a network of accredited centres. The aim of this article is to describe progress in the programme quality over time after the inception of the organised programme. Methods The CBCSP is monitored using an information system consisting of three principal components: 1) the national cancer registry, 2) a screening registry collecting data on all screening examinations, further assessments and final diagnoses at accredited programme centres, and 3) administrative databases of healthcare payers. Key performance indicators from the European Guidelines have been adopted for continuous monitoring. Results Breast cancer incidence in the Czech Republic has steadily been increasing, however with a growing proportion of less advanced stages. The mortality rate has recently stabilised. The screening registry includes 2,083,285 records on screening episodes between 2002 and 2008. In 2007-2008, 51% of eligible women aged 45-69 were screened. In 2008, the detection rates were 6.1 and 3.7 per 1,000 women in initial and subsequent screening respectively. Corresponding recall rates are 3.9% and 2.2%, however, it is necessary to pay attention to further assessment performed during the screening visits. Benign to malignant open biopsy ratio was 0.1. Of invasive cases detected in screening, 35.6% was less than 10 mm in diameter. Values of early performance indicators, as measured by both crude and standardized estimates, are generally improving and fulfil desirable targets set by European Guidelines. Conclusions Mammography screening in the Czech Republic underwent successful transformation from opportunistic prevention to an organised programme. Values of early indicators confirm continuous improvement in different aspects of process quality. Further stimulation of participation through invitation system is necessary to exploit the full potential of screening mammography at the population level.